2010
DOI: 10.1682/jrrd.2009.04.0040
|View full text |Cite
|
Sign up to set email alerts
|

Measuring consonant identification in nonsense syllables, words, and sentences

Abstract: Abstract-Sensorineural hearing loss (SNHL) produces deficits in speech comprehension in noise that primarily are due to impairments in identifying consonants. Here, we describe the California Syllable Test (CaST) that quantifies the identification of common American English consonants. In experiment I, 16 young subjects with normal hearing identified 720 consonant-vowel-consonant (CVC) syllables in three test sessions. Consonants were identified slightly more accurately in words than nonsense syllables, and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…It uses the signal detection measure d to quantify the SNRs necessary to identify each of 20 leading and 20 trailing consonants. In previous studies, we demonstrated that consonants differ substantially in the SNRs required for their identification [16]. Group A consonants (/ʃ/, /ʧ/, /t/, /s/, /z/, /ʤ/, and /r/) in isolated syllables are accurately identified at SNRs near 0 dB, i.e., similar to the SNRs obtained in sentence reception threshold (SeRT) testing of YNH subjects.…”
supporting
confidence: 74%
See 4 more Smart Citations
“…It uses the signal detection measure d to quantify the SNRs necessary to identify each of 20 leading and 20 trailing consonants. In previous studies, we demonstrated that consonants differ substantially in the SNRs required for their identification [16]. Group A consonants (/ʃ/, /ʧ/, /t/, /s/, /z/, /ʤ/, and /r/) in isolated syllables are accurately identified at SNRs near 0 dB, i.e., similar to the SNRs obtained in sentence reception threshold (SeRT) testing of YNH subjects.…”
supporting
confidence: 74%
“…Consonant identification is more accurate in words than nonsense syllables for YNH subjects [16]. If ONH subjects showed reduced lexicality benefits, it would contribute to age-related differences in overall consonant identification thresholds.…”
Section: Lexicality Effectsmentioning
confidence: 92%
See 3 more Smart Citations